نموذج الاستدلال اللغوي: المنهج والبنية - عبدالدايم محمد (University of Eloued جامعة الوادي, 2025)
يلزم لمناقشة العلاقة بين نماذج الاستدلال اللغوي والاستنباط الفقهي والاستنتاج الأرسطي، أن يُفْرد لنموذج الاستدلال الغوي بحث يؤصِّله، ويقف على منهجه وبنيته نظرًا لغياب هذين الأمرين إنْ في الدراسات العربية، وإن في دراسات المستعربين. ويرجع لزوم ذلك إلى كونه حجر الزاوية في هذه النماذج الثلاثة، ولو بالنسبة للباحث بصفته لسانيًّا. ويعالج البحث بُعْدَي المنهج والبنية لنموذج الاستدلال اللغوي بوصفهما المقياس الذي يمكن على أساسه حساب مدى خصوصية النموذج اللغوي. وينطلق البحث من كون الاستدلال بعامَّة آلة إنتاج العلم بنقل الدعوى إلى فكرة ذات دليل؛ ومن ثم يقوم باستخلاص المنهج أو الآلة العقلية التي يملكها الاستدلال اللغوي تحديدًا وتجعله آلة إنتاج المعرفة اللغوية، وهو ما يسميه البحث بمقياس الاستدلال، ويثني بالوقوف على بنية الاستدلال بما تشتمل عليه هذه البنية من مراحل، وإجراءات، ووظائف لهذه الإجراءات. وقد اعتمد في ذلك على مراجعةِ عمليةِ الاستدلالِ، إن كما تقررها كتب الأصول، وإن كما تمارسها الدراسات اللغوية، وقام بتخطيط هذه العملية، لرسم مسارها، والكشف عن آليتها. ويتمثل أهم ما أنجزه البحث في جِدَّة أطروحاته، نحو: مقياس الاستدلال الذي يراه المنهج المعتمد للاستدلال، ومخطط الاستدلال الذي يعكس بنيته، وآليَّة عمل الاستدلال اللغوي التي تعكس فاعليته، وتتيح فهمه، وتُيَسِّر مناقشته في ضوء النماذج المقابلة له إن في العلوم التراثية، وإن في اللسانيات المعاصرة. The Paradigm of Linguistic Inference: Methodology and Structure Abstract Discussing the relationship between paradigms of linguistic inference, jurisprudential deduction, and Aristotelian reasoning necessitates dedicating a study to the paradigm of linguistic inference. Such a study should establish its foundations and delve into its methodology and structure, given the absence of these aspects in both Arabic studies and the works of Arabists. This necessity stems from the paradigm’s role as the cornerstone of these three models, particularly from the perspective of the researcher as a linguist. The study addresses the dimensions of methodology and structure in the paradigm of linguistic inference, considering them as the standard by which the specificity of the linguistic paradigm can be measured. The study begins with the premise that inference, in general, serves as a tool for generating knowledge by transferring a claim into an evidence-supported idea. Consequently, it seeks to extract the methodology or cognitive mechanism specific to linguistic inference, which enables it to function as a tool for producing linguistic knowledge—referred to in the study as the “Inference Standard.” The study then proceeds to examine the structure of inference, encompassing its stages, procedures, and the functions of these procedures. The study relies on reviewing the process of inference as established in the foundational texts of jurisprudence and as practiced in linguistic studies. It then charts this process to outline its trajectory and uncover its underlying mechanism. The study’s most notable accomplishment lies in the novelty of its propositions, such as the “Inference Standard,” which it identifies as the methodology underlying inference; the “Inference Diagram,” which reflects its structure; and the mechanism of linguistic inference, which demonstrates its effectiveness, facilitates its understanding, and simplifies its discussion in light of comparable paradigms, whether in traditional sciences or contemporary linguistics.
مقال . مجلة العلوم العربية
Keywords: النموذج; النظرية; المناهج اللغوية; التراث اللغوي العربي; الاستدلال اللغوي; Paradigm; theory; linguistic approaches; Arabic linguistic tradition; linguistic inference.